2021
DOI: 10.1038/s41467-021-23839-w
|View full text |Cite
|
Sign up to set email alerts
|

When band convergence is not beneficial for thermoelectrics

Abstract: Band convergence is considered a clear benefit to thermoelectric performance because it increases the charge carrier concentration for a given Fermi level, which typically enhances charge conductivity while preserving the Seebeck coefficient. However, this advantage hinges on the assumption that interband scattering of carriers is weak or insignificant. With first-principles treatment of electron-phonon scattering in the CaMg2Sb2-CaZn2Sb2 Zintl system and full Heusler Sr2SbAu, we demonstrate that the benefit o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 80 publications
2
55
0
Order By: Relevance
“…13 and 14 of Supplementary Material we dis-cuss other details of this case, such as estimates of S and the impact of band degeneracy. We note that earlier studies have observed that adding a heavier band is detrimental to electronic conductivity 80,81 , in agreement with our conclusions.…”
Section: Band Convergencesupporting
confidence: 94%
See 1 more Smart Citation
“…13 and 14 of Supplementary Material we dis-cuss other details of this case, such as estimates of S and the impact of band degeneracy. We note that earlier studies have observed that adding a heavier band is detrimental to electronic conductivity 80,81 , in agreement with our conclusions.…”
Section: Band Convergencesupporting
confidence: 94%
“…One of the strategies of using band engineering to design high-performance thermoelectric materials is based on the concept of band convergence, where it is proposed that high degeneracy near conduction or valence band edges is beneficial for increasing σ for a given S due to the presence of multiple conducting channels 3,23,[27][28][29][30][31][32][33][34][35][36][37] . However, several recent studies predicted that the interband scattering can complicate the conventional understanding of the effects of band convergence on the electronic transport properties and that it is not always beneficial for the PF optimization [79][80][81] . Here we revisit the concept of band convergence using the parabolic two-band model within the EPA approximation.…”
Section: Band Convergencementioning
confidence: 99%
“…from intervalley scattering. 41 Engineering the band edges to achieve high band degeneracy is therefore a clear strategy to improve thermoelectric performance. A simple model is needed to engineer the band convergence by doping or alloying.…”
Section: Resultsmentioning
confidence: 99%
“…As early raised by Chasmar and Stratton 6 , the transport coefficients which characterize the thermoelectric efficiency can be written as a function of Fermi integrals in the frame of the semi-classical treatment of the Boltzmann equation within the relaxation time approximation 7 . This description can be extended by including different scattering mechanisms 8 12 , bipolar effects 9 , multiple bands and valley degeneracy 13 17 . If one considers for instance that the relaxation time, the velocity and the density of states vary as a function of the energy according power laws 18 with the exponents , and respectively, then the electrical conductivity , the thermopower and the Lorentz number , with the electronic thermal conductivity , can be defined as it follows 6 , 8 10 .…”
Section: Introductionmentioning
confidence: 99%